Hepatitis Flare During Immunotherapy in Patients With Current or Past Hepatitis B Virus Infection - Wong, Grace Lai-Hung; Wong, Vincent Wai-Sun; Hui, Vicki Wing-Ki; Yip, Terry Cheuk-Fung; Tse, Yee-Kit; Liang, Lilian Yan; Lui, Rashid Nok-Shun; Mok, Tony Shu-Kam; Chan, Henry Lik-Yuen; Chan, Stephen Lam (The American journal of gastroenterology, 2021)
Immunotherapy has dramatically improved the survival of patients with advanced or metastatic malignancies. Recent studies suggest that immunotherapy may increase the risk of hepatitis, whereas it may also induce functional cure of chronic hepatitis B virus (HBV) infection. We evaluated the incidence of hepatitis flare, HBV reactivation, hepatitis B surface antigen (HBsAg) seroclearance or seroreversion in patients with current or past HBV infection who had received immunotherapy. This was a territory-wide observational cohort study in Hong Kong. We identified patients through electronic medical records based on the prescriptions of immune checkpoint inhibitors from July 1, 2014, to December 31, 2019. Patients who were HBsAg positive or HBsAg negative with results for antibody to hepatitis B surface or core antigen (anti-HBs or anti-HBc) were included. A total of 990 patients (397 HBsAg-positive, 593 HBsAg-negative with 482 anti-HBc and/or anti-HBs positive, and 111 both anti-HBc and anti-HBs negative) were identified. All of HBsAg-positive and 15.9% HBsAg-negative patients were put on oral antiviral treatment. Hepatitis flare (alanine aminotransferase >2 times of the upper limit of normal) occurred in 39.3% HBsAg-positive and 30.4% HBsAg-negative patients. High baseline alanine aminotransferase and combination of immunotherapy increased the risk of hepatitis. HBV reactivation (≥2 log increase in HBV DNA from baseline) occurred in 2 HBsAg-positive patients; HBsAg seroclearance and seroreversion was observed in 1 HBsAg-positive and 1 HBsAg-negative patient, respectively (<1%). Hepatitis flare occurs in approximately 40% of HBsAg-positive patients and 30% of HBsAg-negative patients during immunotherapy. HBV reactivation, HBsAg seroclearance, and HBsAg seroreversion are rare. Current or past HBV infection has no impact on the emergence of hepatic flare associated with immunotherapy.